General practice registrars' experiences of antenatal care: A cross‐sectional analysis. (19th August 2019) - Pappalardo, Emma; Magin, Parker; Tapley, Amanda; Davey, Andrew; Holliday, Elizabeth G.; Ball, Jean; Spike, Neil; FitzGerald, Kristen; Morgan, Simon; van Driel, Mieke L.
Abstract : Background: General practitioners play an important role in diagnosis and ongoing management of pregnancies. Some GP registrars entering GP training may have had no post‐graduate experience in obstetrics and gynaecology. GP registrars' involvement in antenatal care is under‐researched. Aims: This study aimed to determine the prevalence and associations of Australian GP registrars' clinical consultations involving antenatal care. Materials and Methods: A cross‐sectional analysis from the Registrar Clinical Encounters in Training (ReCEnT) cohort study. GP registrars record details of 60 consecutive consultations during each of three six‐month training terms. Associations of managing pregnancy‐related problems (compared to all other problems) were analysed using univariate and multivariable logistic regression. Independent variables included registrar, practice, patient, consultation and educational factors. Results: Antenatal care comprised 3277 (1.1%) of registrar problems/diagnoses. Consultations involving pregnancy‐related problems were significantly associated with registrars being female, in term three, younger, and having post‐graduate qualifications in obstetrics/gynaecology. Patients were significantly more likely to be from a non‐English speaking background. Pregnancy‐related problems/diagnoses were more likely to be seen in lower socioeconomic areas. Consultation factors significantly associated with a pregnancy‐related problem/diagnosis included ordering imaging, ordering pathology, arranging referrals, and a longer duration of consultation. Registrars were less likely to prescribe medication or generate learning goals. Conclusions: GP registrars see fewer antenatal problems compared to established GPs. Male registrars, especially, have significantly less exposure to antenatal care, suggesting potential limitation of opportunity to gain skills and experience in antenatal care.